A study on relationship of employer brand dimensions on job satisfaction: a case study of TH Hotel and Residence / Mohd Azri Hanin Akbar - Akbar, Mohd Azri Hanin (2016)
This research is an attempt to investigate the relationship of employer branding on job satisfaction in TH Hotels and Residence. Over 193 questionnaires were distributed during the study. The researcher identified that there are five (5) independent variables which is the SERVQUAL involved in this study namely Training and Development, Reputation, Work-Life Balance, CSR, Organizational Culture and Diversity. In the findings, it is shown that Work-Life Balance has an insignificant relationship with the dependent variable which can be determine as weakest dimensions and need to be improve. The dependent variable in this study is the level of job satisfaction of TH Hotel staff. Respondent involved in this study are selected in non-probability sampling among staff who are happens to be the employee of TH Hotel and Residence.